Shaping Superior Learners Through Digitalization Of Indonesian Language Learning According to The Independent Curriculum - Ali, Almuhtadi Billah; Ali, Muttaqin Kholis; Ali, Rahmi Imanda; Hasanah, Arrahmil (Jurnal Hata Poda, 2024)
The Independent Curriculum has inspired profound changes in the Indonesian education system, emphasizing the importance of adapting to technological advancements. This research aims to explore how the digitalization of Indonesian language learning can be a crucial strategy in forming excellent students in line with the spirit of the Independent Curriculum. The research methodology used is a quantitative survey approach. The main findings indicate that the integration of technology in Indonesian language learning has a positive impact on the accessibility of learning materials, students' language abilities, and character development. These results reinforce the idea that digital learning can be an effective means to enhance the quality of Indonesian language education. Practical implications include the development of relevant digital content, training for educators in integrating technology, and collaboration among various stakeholders. Recommendations for further development include further research on practical barriers, the development of diverse digital content, collaborative efforts in digital infrastructure development, and continuous evaluation of the implementation of digitalization in Indonesian language learning